2004
DOI: 10.1128/jvi.78.15.8349-8358.2004
|View full text |Cite
|
Sign up to set email alerts
|

Global Identification of Three Major Genotypes of Varicella-Zoster Virus: Longitudinal Clustering and Strategies for Genotyping

Abstract: By analysis of a single, variable, and short DNA sequence of 447 bp located within open reading frame 22 (ORF22), we discriminated three major varicella-zoster virus (VZV) genotypes. VZV isolates from all six inhabited continents that showed nearly complete homology to ORF22 of the European reference strain Dumas were assigned to the European (E) genotype. All Japanese isolates, defined as the Japanese (J) genotype, were identical in the respective genomic region and proved the most divergent from the E strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
252
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(271 citation statements)
references
References 44 publications
10
252
1
8
Order By: Relevance
“…PCR amplifications of the ORF21 -502 bp target region, ORF22 -447 bp target region, ORF50 -514 bp target region were performed with a GeneAmp PCR System 9700 (Applied Biosystems, Carlsbad, CA) using 5 μl of DNA extracted from skin lesions of the patient. PCR products were separated on 4% precast gradient polyacrylamide gels prestained with ethidium bromide (Invitrogen) and visualized under UV irradiation alongside a 100-bp ladder (Invitrogen) [7][8][9]11,12 . Similar methods were used for multi-locus DNA sequence analysis at ORF 1,6, 9 and 28.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…PCR amplifications of the ORF21 -502 bp target region, ORF22 -447 bp target region, ORF50 -514 bp target region were performed with a GeneAmp PCR System 9700 (Applied Biosystems, Carlsbad, CA) using 5 μl of DNA extracted from skin lesions of the patient. PCR products were separated on 4% precast gradient polyacrylamide gels prestained with ethidium bromide (Invitrogen) and visualized under UV irradiation alongside a 100-bp ladder (Invitrogen) [7][8][9]11,12 . Similar methods were used for multi-locus DNA sequence analysis at ORF 1,6, 9 and 28.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated a distinctive geographic distribution of the major VZV genotypes aligning with cool versus warm climate regions of the globe 6 . It is unclear whether the strain distribution is actually driven by climate or/and other factors, such as immigration patterns [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations